Tasawwuf al-Dihlawi menghadapi kebejatan akal dan akhlak zamannya - Mohd Amin, Wan Mohd Azam (2010)
AÍmad ibn ÑAbd al-RaÍÊm al-Dihlawi, popularly known as Shah WaliullÉh al-DihlawÊ was one of the great Islamic scholars in the Muslim world as he mastered many Islamic sciences such as tafsÊr, ÍadÊth, tasawwuf, fiqh and others. Following the step of his predecessors like al-MakkÊ, al-GhazÉlÊ and Sirhindi, he attempted to to reform (iÎlaÍ) the muslim society by synthesising between various sciences in Islam including Sufism and SharÊÑah, ÍadÊth, fiqh al-madhÉhib and others. In Sufism, ShÉh Waliullah went a step further in harmonizing between two contradictory theories in Sufism i.e. waÍdat al-wujËd of Ibn ÑArabÊ and waÍdat al-shuhËd of Sirhindi. Moreover, he introduced his own framework of Sufism which was the amalgamation of previous Sufi practices, traditionalist (muÍaddith), theologian (mutakallim), jurist (fiqh) and other methodologies. This framework which was known as ÙarÊq ShÉh WalÊ AllÉh aims at reforming Sufism and ethics (akhlÉq) of muslim society.